Anemia at the first prenatal visit in a health center in Lima, Peru, and its relationship with the pregestational nutritional status - Taipe-Ruiz, Blanca Regina (2019)
Objective: To determine the frequency of anemia in pregnant women and its relationship with the pregestational nutritional status. Materials and methods: A descriptive, observational, cross-sectional and retrospective study was carried out in the Obstetrics and Nutrition Department of the Centro de Salud de Surco between July 1, 2015 and July 31, 2016. Four hundred fifty-five (455) maternal perinatal medical records (HCMP) from the Obstetrics Department of the Centro de Salud de Surco were reviewed, out of which 93 met the inclusion criteria and were selected. Descriptive statistics was used. Results: Eleven point eight percent (11.8 %) of the pregnant women presented anemia. The average hemoglobin level in the aforementioned women was 12.2 ± 1.06 g/dl. Fifty-eight point five percent (58.5 %) had a normal pregestational body mass index (BMI) and the highest frequency of anemia (10.7 %). It was observed that cases of anemia were more frequent in the first two quarters of pregnancy, reaching on average 4.8 %, and decreased in the third quarter (2.2 %). Conclusions: The highest frequency of anemia in pregnant women occurred in the normal pregestational BMI group. Hemoglobin levels decrease according to the age of the mother and increase according to the gestational age.